Simulation of the role of vibration on Scanning Vibrating Electrode Technique measurements close to a disc in plane. (10th June 2016) - Dolgikh, Olga; Demeter, Andrei–Stefan; Lamaka, Sviatlana V.; Taryba, Maryna; Bastos, Alexandre C.; Quevedo, Marcela C.; Deconinck, Johan
Abstract: An elegant and accessible way to account for the local stirring created by the vibration of the SVET tip by adding a new diffusion–like term into the molar flux expression is proposed, in order to avoid solving the fluid flow. This term is maximal in the point of vibration and rapidly decreases with the distance. It is shown that the local mixing leads to a substantial increase of the migration current density in the vicinity of the probe with simultaneous decrease of the diffusion current contribution. This local mixing has no effect on the pH distribution, regardless the applied polarization, and increases under cathodic polarization the oxygen concentration only when the probe is close to the electrode surface which is confirmed by experimental observations. The proposed model is compared with the analytical current density distributions obtained from potential model and experimental data. All this indicates that local mixing might explain why the SVET technique, although based on the measurement of an ohmic current density, measures always the total current density.